Brazing TC4 alloy to Si3N4 ceramic using nano-Si3N4 reinforced AgCu composite filler. (5th July 2015) - Zhao, Y.X.; Wang, M.R.; Cao, J.; Song, X.G.; Tang, D.Y.; Feng, J.C.
Graphical abstract: Interfacial microstructure of TC4/Si3 N4 joints brazed using (a) AgCu eutectic filler treated by ball-milling and (b) nano-Si3 N4 reinforced AgCu composite filler at 880 °C for 10 min. The use of composite filler promoted the formation of Ag based composite reinforced by fine particles in brazing seam, which improved the interfacial microstructure and shear strength of TC4 /Si3 N4 brazed joints, as shown in figure (c). Highlights: Brazing of TC4 to Si3 N4 was achieved with nano-Si3 N4 reinforced AgCu filler. Nano-Si3 N4 addition suppressed the growth of brittle compound layers in joints. Nano-Si3 N4 addition could improve the shear strength of TC4/Si3 N4 brazed joints. Interfacial microstructural morphology depended on the brazing temperature. Abstract: A novel particle reinforced AgCu composite filler (abbreviated as AgCuC filler) was developed by introducing nano-Si3 N4 particles and micron-Ti particles into AgCu powder filler. Reliable brazing of TC4 alloy to Si3 N4 ceramic was achieved by using the AgCuC filler. The interfacial microstructure of TC4/AgCuC /Si3 N4 brazed joint was TC4/Ti–Cu intermetallic layers/Ag based composite reinforced by fine particles/TiN + Ti5 Si3 layer/Si3 N4 . The addition of nano-Si3 N4 in AgCuC filler improved the interfacial microstructure by suppressing the growth of continuous Ti–Cu intermetallic layers adjacent to TC4 alloy and promoting the formation of Ag based composite reinforced by particle phases in brazing seam. The continuous Ti–Cu intermetallic layers thicken and the TiCu2 particle phases coarsened gradually with an increasing brazing temperature. Brazing defects including micro-cracks and nano-Si3 N4 aggregation were generated at higher brazing temperature. The highest average shear strength of 73.9 MPa was achieved when brazed at 880 °C for 10 min, which was higher than that of joints brazed using AgCu filler alone (49.2 MPa).